ChemInform Abstract: Taming Furfuryl Cations for the Synthesis of Privileged Structures and Novel Scaffolds. Issue 43 (7th October 2013) - Dhiman, Seema; Ramasastry, S. S. V.
Abstract The reaction of furfuryl cations generated from furfuryl alcohols towards nucleophilic substitution is investigated.